Social Studies for Civic Education Practice in Japan: a Case Study of Human Rights Learning through Participatory Approach in Junior High School 3rd Grade - Katsuhisa Shirai (The Indonesian Journal of Social Studies, 2020)
This research aims to emphasize the characteristics of social studies for civic education practice in Japan through a case study of junior high school 3rd grade practice of œhuman rights learning through participatory hands-on learning and to show comparative viewpoints on social studies in Indonesia. The following points became clear as a result of this research. First, through the unit of social studies and civic education, students could have fun and realize the value of human rights by adopting a participatory experiential approach to learning with the inclusion of workshops and simulated trials. This point is one of the important characteristics of citizenship in a democratic society. Second, in a social studies and civic education class, the students actively respected others opinions and learned from each other by actively participating in group activities and discussions. This point forms the basis of the citizenship necessary to form a democratic society. The above two points are thought to have implications for the social studies for civic education in Indonesia.